PENGARUH EFEKTIFITAS PENGGUNAAN MODEL SIMULASI TERHADAP PEMAHAMAN MATERI DEMOKRASI - Anggun Septiana; Holilulloh Holilulloh; Hermi Yanzi (FKIP Unila, 2016)
The research aimed to analyze and describe the effect of the use of simulation models to the democracy material understanding at VIIIA class in SMP Negeri 2 Tulang Bawang Barat academic year 2015/2016. The method used in this research was quasi-experimental method. The population in this study research was quasi-experimental method. The population in this study was 38 students grade VIIIA as the experimental class and 38 students grade VIIIB as the control class. The data in this research were collected through a test of understanding, supported by documentation and observation techniques, data analysis technique was using the t-test formula. The results showed that there is a positive effect of the use of simulation models to increase the understanding of democracy in the class VIIIA of SMP Negeri 2 Tulang Bawang Tengah. This was demonstrated through experimental class student learning outcomes which are greater than the control class learning outcomes. Where as the experimental class students have an average value of 7.05 and a control class has average value of 6.42.Penelitian ini bertujuan untuk menganalisis dan mendeskripsikan pengaruh penggunaan model simulasi terhadap pemahaman materi demokrasi kelas VIIIA di SMP Negeri 2 Tulang Bawang Tengah tahun pelajaran 2015/2016. Metode yang digunakan penelitian ini adalah menggunakan metode eksperimen semu. Populasi dalam penelitian ini sekaligus dijadikan sample yaitu 38 siswa kelas VIIIA (kelas eksperimen) dan 38 siswa keas VIIIB (kelas kontrol). Data dalam penelitian ini dikumpulkan melalui tes pemahaman, ditunjang oleh teknik dokumentasi dan pengamatan, teknik analisa data menggunakan rumus uji t. Hasil penelitian menunjukkan bahwa terdapat pengaruh positif penggunaan model simulasi dalam meningkatkan pemahaman materi demokrasi di kelas VIIIA SMP Negeri 2 Tulang Bawang Tengah. Hal ini ditunjukkan melalui hasil belajar siswa kelas eksperimen lebih besar yaitu7,05 dan kelas kontrol yaitu 6,42.Kata kunci: efektifitas, model simulasi, pemahaman materi demokrasi.